Literature as identity building locus: A fictional approach to the conflicts raised around urban consolidation in Perú - Diez Canseco Carranza, Jesús José (Espergesia, 2018)
The text proposal is focused in a socio-literary field. Introduced herein are interdisciplinary processes with the purpose of constructing, from the Julio Ramon Ribeyro urban narrative, a relational-textual system. Qualitatively joining with the sociology of literature, cultural anthropology and literary phenomenology, this study describes the philosophical and socio-anthropological categories typical of the Peruvian identity starting from the national urban-realistic literature; identifying social forms of approach from the urban-realistic literature and establishing epistemological relationships between the Peruvian urban-realistic literature and society, and thus to consolidate interpretative and identity strategies that start from the relationship between text and society in Peru. The more striking findings bring us close to a national identity not consubstantial, which is evident in the urban space and impact of its structural conformation. Likewise it reveals socio-cultural post modern coordinates, the same ones that are strengthened thanks to the relationship approached between urban-realistic literature and society.